Heterosexual penile/anal intercourse and HIV in five sub-Saharan African countries - Duby, Zoe (Department of Public Health and Family Medicine, 2015)
The HIV epidemic in sub-Saharan Africa is understood to be primarily 'sexually transmitted'. The majority of HIV prevention efforts in the region have focused on 'heterosexual sex' as the key transmission vector, without defining what 'heterosexual sex' refers to. Penile-anal intercourse (PAI) has the highest per act risk of HIV acquisition sexually and potentially accounts for a large proportion of HIV infection. Inclusion of PAI in HIV programming has typically only been in reference to men who have sex with men. Despite evidence suggesting that heterosexual PAI is common practice in sub-Saharan Africa, and is likely to be a significant contributor to HIV transmission, it has been largely excluded from HIV interventions. Greater understanding of sexual decision-making and risk-taking related to heterosexual PAI would enable evidence-based HIV intervention. This thesis presents data on conceptualisations and perceptions of heterosexual PAI and associated practices in sub-Saharan Africa, language and discourse pertaining to PAI, as well as challenges in conducting research on it. Qualitative data were gathered in five sub-Saharan African countries between 2010 and 2014. These findings demonstrate that heterosexual PAI is practiced in sub-Saharan Africa for a variety of reasons, some of which have implications for HIV transmission. Many of the factors that influence sexual decision-making and risk-taking related to heterosexual PAI are specific to this sexual behaviour. In addition, the relationship contexts in which heterosexual PAI takes place, gendered power dynamics, sexual agency and 'sexual scripts' framing PAI behaviour, are distinct from those for penile/vaginal intercourse. HIV transmission risks associated with PAI are exacerbated by taboos, social stigmatisation and sexual communication norms, impeding effective communication and safe sex negotiation, limiting individuals' ability to make informed decisions, and impacting on the reporting of PAI in research and clinical settings. Drawing on socio-behavioural theories to guide the data analysis, I developed theoretical models to explain and understand heterosexual PAI practice. The findings presented in this thesis make a unique contribution to the field, being the first in-depth description and analysis of heterosexual PAI behaviour and related practices in sub-Saharan Africa. This research highlights the importance of paying careful attention to the role of heterosexual PAI in HIV transmission in Africa.